1997
DOI: 10.1017/s0142716400009887
|View full text |Cite
|
Sign up to set email alerts
|

Word recognition from acoustic onsets and acoustic offsets: Effects of cohort size and syllabic stress

Abstract: In the traditional gating technique, subjects hear increasing amounts of word-onset information from spoken words until the words can be correctly identified. The experiment reported here contrasted word-onset gating with results when words were gated from their word endings. A significant recognition advantage for words gated from their onsets was demonstrated. This effect was eliminated, however, when we took into account the number of word possibilities that shared overlapping phonology and the same stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…In fact, overreliance on word-initial information would produce serious comprehension difficulties whenever word-initial errors are made by either the speaker or the listener. Although word-initial information may be given priority, listeners can recognize words on the basis of partial information even in backward gating tasks (Salasoo & Pisoni, 1985;Walley, 1988;Wingfield et al, 1997). More recent versions of the cohort model acknowledge these difficulties (Gaskell & Marslen-Wilson, 1999;Marslen-Wilson, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, overreliance on word-initial information would produce serious comprehension difficulties whenever word-initial errors are made by either the speaker or the listener. Although word-initial information may be given priority, listeners can recognize words on the basis of partial information even in backward gating tasks (Salasoo & Pisoni, 1985;Walley, 1988;Wingfield et al, 1997). More recent versions of the cohort model acknowledge these difficulties (Gaskell & Marslen-Wilson, 1999;Marslen-Wilson, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Adults can recognize words on the basis of partial word-initial or even word-final information (Grosjean, 1980;Marslen-Wilson, 1987;Marslen-Wilson & Welsh, 1978;Salasoo & Pisoni, 1985;Walley, 1988;Wingfield, Goodglass, & Lindfield, 1997), suggesting that word recognition proceeds on the basis of matching partially analyzed input with segmentally organized lexical representations in memory. This phenomenon most typically has been studied using a gating task in which participants hear successively longer fragments of words, for instance, beginning with the initial (or final) 50 ms and increasing by small increments until participants can reliably identify the words without any subsequent change in response.…”
Section: Evidence From Gating Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, findings suggest that word recognition in adults is also partially determined by the location of the uniqueness point (Kwantes & Mewhort, 1999;Lindell, Nicholls, Kwantes, & Castles, 2005; but see Lamberts, 2005). This variable, initially manipulated in auditory word-recognition studies (e.g., Marslen-Wilson, 1984;Radeau & Morais, 1990;Wingfield, Goodglass, & Lindfield, 1997), is defined as the point (phoneme) in the target word where only one lexical candidate remains, given the sequential property of speech. Transposed to reading, the orthographic point of uniqueness corresponds to the serial position of the letter in the word where only one lexical candidate remains, considering the letter strings serially from left to right.…”
Section: Main Variables In the Study Of Literacy Acquisition: A Shortmentioning
confidence: 99%
“…In her discussion of the potential importance of wordinitial information during spoken word recognition, Walley (1988) noted that word-initial information reaches the listener first (especially pertinent in view of the transience of the speech waveform) and that word-initial information is more resistant to change by phonological processes. Indeed, studies in which a variety of paradigms were used, including noise replacement /addition and gating, have shown that word-initial information facilitates spoken word recognition more than does word-final information (e.g., Cole & Jakimik, 1980;Nooteboom, 1981;Salasoo & Pisoni, 1985;Walley, 1988;Wingfield, Goodglass, & Lindfield, 1997).…”
Section: Discussionmentioning
confidence: 99%